Corn Cost-Return Budget in Northeast Kansas - Fogleman, Sarah L.; Duncan, Stewart R. (My University, 2006)
This publication projects a budget that reflects expected income and costs based on typical corn production practices in northeastern Kansas.
MF571_2006_10
Keywords: MF571; Economics; Crops; MF